Diffusion Tensor Imaging in Rat Models of Preclinical Diabetic Nephropathy: A Preliminary Study - Hu, Xiaoyan; Kuang, Min; Peng, Bo; Yang, Yang; Lin, Wei; Li, Wenbo; Wu, Yinghua (Frontiers in Endocrinology, 2021)
Purpose This study aimed to investigate the value of diffusion tensor imaging to assess renal injury in a rat model of preclinical diabetic nephropathy. Methods Twenty-eight male Sprague Dawley rats were divided into two groups: the normal control (NC) group of 10 rats and the diabetic nephropathy (DN) group of 18 rats. Eight weeks after diabetes induction by streptozotocin, 3.0-T magnetic resonance (MR) imaging (b = 0 and 600 s/mm2, 15 diffusion directions) using a 32-channel knee coil was performed. After MR imaging, we measured serum creatinine, and collected double kidney tissues for pathology. The apparent diffusion coefficients(ADC) and fractional anisotropy(FA) values of the renal cortex and medulla were calculated for all kidneys. Physiological parameters, laboratory parameters, and imaging results were compared between the two groups. Results All DN group animals developed hyperglycemia, polyuria, and emaciation. Serum creatinine was not significantly different between the groups (P > 0.05). Urinary albumin at 2, 4, and 8 weeks was higher in the DN group than in the NC group but <20 µg/min (P < 0.05). Pathologically, renal damage in the DN rats was observed. The ADC value was significantly increased in DN animals in the cortex (1.75×10-3mm2/s),medulla(1.53×10-3mm2/s)compared with NC group(cortex, 1.52×10-3mm2/s; medulla,1.35×10-3mm2/s). The FA value was significantly reduced in DN animals in the cortex (0.21),medulla(0.25)compared with NC group(cortex,0.26;medulla,0.3). Conclusions Increased apparent diffusion coefficients and decreased fractional anisotropy values on diffusion tensor imaging were associated with preclinical DN. Diffusion tensor imaging may be useful in early, non-invasive, quantitative detection, and therapy monitoring of DN.